3rd PERPUN International Conference 2013 : Strategic Library Services : Evilving Library in new directions - Centre for Academic, Information Services (Centre for Academic Information Services, UNIMAS, 2013)
This conference will help participants gain an insight on strategic library services. it's a unique combination of knowledge, techniques and methods that the most dramatically successful customer service operations all share. participant will leave this conference with an in-dept knowledge on the best ways to handle difficult customers, to provide information, fact and data that the customers need, motivate others, acquire new knowledge, put "something' extra into every customer contact and much, much more. that's make this conference so valuable.